A LITERARY REVIEW ON SAPINDUS TRIFOLIATUS (GASPENELA) AND ITS MEDICINAL VALUES (International Journal of Ayurveda and Pharma Research, 2021)
Sapindus trifoliatus is a large tree used in treatment of numerous ailments. Its fruits, known as soap nuts, contain Saponin and are widely used in cosmetics. Fruits, skin of the fruit, seeds and leaves are used in medicine internally and externally. Knowledge on medicinal uses of Sapindus trifoliatus is scattered. Therefore, it was decided to gather and record this dispersed information. Data was collected from Ayurveda and Sri Lankan medical books, journals, physicians and through web search. Sapindus trifoliatus is used to conduct Vamana Karma, Virechana Karma and Nasya Karma. It is used in treatment of migraine, epilepsy, bronchial asthma, cough and burning sensation. It is also used in preparation of body shampoo, hair shampoo and detergents. Anti- ulcer, anthelmintic, anti-inflammatory, muscle relaxant, anti-acne and anti-dandruff effect of Sapindus trifoliatus is scientifically proven. Leaf extract was found to be non-toxic up to 2g/kg but frequent administration in high doses elevate in aspartate aminotransferase, alanine aminotransferase, blood urea and serum creatinine in rats. It is concluded that Sapindus trifoliatus has multifaceted medicinal values.